Bovine Animal Model for Studying the Maternal Microbiome, in utero Microbial Colonization and Their Role in Offspring Development and Fetal Programming - Amat, Samat; Dahlen, Carl R.; Swanson, Kendall C.; Ward, Alison K.; Reynolds, Lawrence P.; Caton, Joel S. (Frontiers in Microbiology, 2022)
Recent developments call for further research on the timing and mechanisms involved in the initial colonization of the fetal/infant gut by the maternal microbiome and its role in Developmental Origins of Health and Disease (DOHaD). Although progress has been made using primarily preterm infants, ethical and legal constraints hinder research progress in embryo/fetal-related research and understanding the developmental and mechanistic roles of the maternal microbiome in fetal microbial imprinting and its long-term role in early-life microbiome development. Rodent models have proven very good for studying the role of the maternal microbiome in fetal programming. However, some inherent limitations in these animal models make it challenging to study perinatal microbial colonization from a biomedical standpoint. In this review, we discuss the potential use of bovine animals as a biomedical model to study the maternal microbiome, in utero microbial colonization of the fetal gut, and their impact on offspring development and DOHaD.